Data-Driven Marketing Strategies : Optimizing Dental Supply Marketing Through Cluster Analysis - Sládková, Simona; Průša, Přemysl, 1980-; Svoreň, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores the application of data-driven marketing strategies in the dental supply sector, with a specific focus on DentX, a leading Slovak dental supply company. Recognizing the limitations of traditional B2B marketing approaches in highly specialized industries, this study employs cluster analysis to segment DentX’s client base and develop more targeted and effective marketing strategies. By analyzing real-world purchasing and operational data, five distinct clusters of dental clinics were identified based on clinic size, patient capacity, and purchasing behavior. These insights were supplemented with qualitative data from interviews with sales representatives. The study highlights the value of personalized marketing, tailored service offerings, and strategic customer engagement to optimize market reach and customer satisfaction in the dental supply industry. The findings demonstrate how data analytics can enhance decision-making and competitive advantage in B2B marketing environments.
Vedoucí práce: Přemysl Průša
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses